GbFLSa overexpression negatively regulates proanthocyanin biosynthesis - Guo, Jing; Wu, Yaqiong; Wang, Tongli; Xin, Yue; Wang, Guibin; Zhou, Qi; Xu, Li-An (Frontiers in Plant Science, 2023)
Flavonoids are important secondary metabolites with extensive pharmacological functions. Ginkgo biloba L. (ginkgo) has attracted extensive attention because of its high flavonoid medicinal value. However, little is understood about ginkgo flavonol biosynthesis. Herein, we cloned the full-length gingko GbFLSa gene (1314 bp), which encodes a 363 amino acid protein that has a typical 2-oxoglutarate (2OG)-Fe(II) oxygenase region. Recombinant GbFLSa protein with a molecular mass of 41 kDa was expressed in Escherichia coli BL21(DE3). The protein was localized to the cytoplasm. Moreover, proanthocyanins, including catechin, epicatechin, epigallocatechin and gallocatechin, were significantly less abundant in transgenic poplar than in nontransgenic (CK) plants. In addition, dihydroflavonol 4-reductase, anthocyanidin synthase and leucoanthocyanidin reductase expression levels were significantly lower than those of their CK counterparts. GbFLSa thus encodes a functional protein that might negatively regulate proanthocyanin biosynthesis. This study helps elucidate the role of GbFLSa in plant metabolism and the potential molecular mechanism of flavonoid biosynthesis.